Drug-Triggered and Cross-Linked Self-Assembling Nanofibrous Hydrogels - Kumar, Vivek A; Shi, Siyu; Wang, Benjamin K; Li, I-Che; Jalan, Abhishek A; Sarkar, Biplab; Wickremasinghe, Navindee C; Hartgerink, Jeffrey D (Journal of the American Chemical Society, 2015)
Self-assembly of multidomain peptides (MDP) can be tailored to carry payloads that modulate the extracellular environment. Controlled release of growth factors, cytokines, and small-molecule drugs allows for unique control of in vitro and in vivo responses. In this study, we demonstrate this process of ionic cross-linking of peptides using multivalent drugs to create hydrogels for sustained long-term delivery of drugs. Using phosphate, heparin, clodronate, trypan, and suramin, we demonstrate the utility of this strategy. Although all multivalent anions result in good hydrogel formation, demonstrating the generality of this approach, suramin led to the formation of the best hydrogels per unit concentration and was studied in greater detail. Suramin ionically cross-linked MDP into a fibrous meshwork as determined by scanning and transmission electron microscopy. We measured material storage and loss modulus using rheometry and showed a distinct increase in G′ and G″ as a function of suramin concentration. Release of suramin from scaffolds was determined using UV spectroscopy and showed prolonged release over a 30 day period. Suramin bioavailability and function were demonstrated by attenuated M1 polarization of THP-1 cells compared to positive control. Overall, this design strategy has allowed for the development of a novel class of polymeric delivery vehicles with generally long-term release and, in the case of suramin, cross-linked hydrogels that can modulate cellular phenotype.